Multicentre narrative research on major depression to integrate the experiences of patients, their caregivers and healthcare providers in Italy. Issue 10 (10th October 2022) - Chesi, Paola; Mencacci, Claudio; Balestrieri, Matteo; Pompili, Maurizio; Varia, Salvatore; Sagripanti, Ubaldo; Reale, Luigi; Marini, Maria Giulia
Abstract : Objective: This research aimed to investigate the experience of major depression by integrating the perspectives of patients, caregivers and healthcare providers through narrative-based medicine (NBM) to provide new insights to improve care relationships. Design and setting: The research was conducted in 2019 and involved five Italian psychiatric centres and targeted adult patients, their caregivers and healthcare providers to address data source triangulation. A sociodemographic survey and a narrative plot, based on Natural Semantic Metalanguage were collected. Narratives were analysed through NBM classifications, NVivo software and interpretative coding. Participants: Thirty-six patients with a diagnosis of major depression, 27 caregivers and 33 healthcare providers participated in the research. Results: Among the 96 collected narratives, 'lonely' was the word patients used most frequently, while 'sad' and 'lifeless' were used most respectively by caregivers and healthcare providers. A positive care relationship was crucial for 84% of patients in relation to their care pathway, and nature (36%) and the arts (28%) were the most frequent resources. Caregivers expressed feelings of powerlessness and inadequacy, and 21% of them reported a declining social life while providing care to a loved one with depression. Thirty-one percent of mental health professionals experienced difficulties in their first encounter with patients; however, their emotions progressively moved towards trust and satisfaction. Furthermore, 89% of patients and healthcare providers and 58% of caregivers evaluated writing the narrative to be a positive experience. Conclusion: Findings suggested the possible role for language in understanding major depression, thereby improving care relationships between patients and physicians. Care pathways might also be more attentive to caregivers, to reduce their risk of burnout. Finally, narrative medicine could be integrated with the care pathway as an additional space of expression, dialogue, reflection and development of empathy.